(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Recent excavations and published accounts of the necropolis of Medellín permit an improved understanding of the corpus of the South-western (SW) inscriptions and their language. It now appears that the same language and epigraphic tradition as known from approximately 80 inscriptions from south Portugal were in use in their fully developed form on the upper Guadiana in the mid 7th century BC. Versions of the same group name were in use in both areas: Kunetes and Konioi. These can be compared with Celtic group names. The fragmentary Medellín stela (J.57.1; T1 86H/En12-1) shows elements of the recurrent Tartessian epigraphic formula. If the SW formula words ro and uar(n)baan correspond to Celtiberian ro and VERAMOS/VORAMOS, then the language of the formula is Indo-European and loses *p.